PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN MENULIS DAN PRESTASI BELAJAR - Emi Deshartika; Johanes Sapri (UNIB Press, 2022)
This research aims to describe the Inquiry learning model which can improve the writing skills, the learning achievement and the effectiveness of the application of the Inquiry learning model which can improve the learning achievement of grade VII students of MTs Negeri 1 Pagaralam. The types of research is Classroom Action Research (CAR) and quasi- experiments, The method used in this study was a mixed method research which is a combination of action research and experimental research The stages of the research carried out were 1) Planning Stage, 2) Implementation Stage, 3) Observation Stage, 4) Reflection Stage. The subjects of this research were students of class VII MTs Negeri 1 Pagaralam in semester 2 of the 2020/ 2021 academic year. The number of students for the CAR class is 32 people, for the Experiment class 33 people, and for the Control class 31 people. The data collection method in this research used the Inquiry learning model observation sheet, observation sheet on students' writing skills and learning outcomes tests. The data analysis used an average score and a test which consisted of a different test between cycles and a two-sample difference test that was not related. The results showed that the application of the Inquiry learning model could improve writing skills, learning achievement and the effectiveness of student learning outcomes in English